First the seed: Genomic advances in seed science for improved crop productivity and food security. Issue 3 (14th March 2021) - Dwivedi, Sangam L.; Spillane, Charles; Lopez, Francesca; Ayele, Belay T.; Ortiz, Rodomiro
Abstract: Seeds are valuable sources of carbohydrates, lipids, proteins, fibers, minerals, and vitamins. They provide energy and nutrition to germinating seedlings, food to humans, feed to livestock, and feedstocks to industry. High‐throughput analyses of gene expression in crops has identified many candidate genes associated with seed dormancy, longevity, germination, and vigor. In this review, we cover the latest research focusing on such key seed traits. Transcriptome analyses of time courses of seed filling have identified sets of genes expressed at different stages of this process. The potential role of epigenetics (including seed–endosperm imprinted genes) in regulating seed development and chemistry is highlighted herein. We also discuss how advances in genomics and seed biology are facilitating the unravelling of associations between seed traits with gene bank accessions and gene sequences, including how functional research can accelerate the discovery of allelic variants. Such knowledge of functional effects relating to gene variants is necessary for more efficient and cost‐effective management of genetic resources or for redesigning crops with specific seed characteristics. For instance, gene bank curators may assess seed viability by monitoring changes in gene expression of biomarker genes in dry seed samples to decide germplasm regeneration and assess genetic integrity of collections by monitoring changes in diversity and allele frequencies between samples of same accession stored in gene banks. We highlight that resistance to preharvest sprouting can be enhanced through genomics‐assisted breeding in otherwise nondormant rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.) cultivars, while pimt, another valuable marker for seed longevity, may be deployed to enhance seed vigor in crops. Core Ideas: Hyperspectral image‐based and spectroscopy analysis enable large‐scale seed trait phenotyping Rebalancing seed chemistry for better nutritional traits appears to be achievable Enhanced knowledge on stage‐dependent seed development and orchestration of gene expression Imprinted genes contribute to seed development, notably to the endosperm Genes and DNA markers linked with seed traits to enhance gene bank and crop breeding efficiency